Comparative Study of the Effect of Service Quality on Nasabah Satisfaction (Bank Muamalat Indonesia Probolinggo Branch and BSI KCP Probolinggo Sudirman) - Nurarifa Suhma, Putriana; Milla, Hayatul (Tazkia Islamic University College, 2024)
This study aims to determine the comparative or different effect of service quality on customer satisfaction at two different banks, namely Bank Muamalat Indonesia Probolinggo Branch and BSI KCP Probolinggo Sudirman. The population of this research is all customers of Bank Muamalat Indonesia Probolinggo Branch and BSI KCP Probolinggo Sudirman. While the method used in this study is a random sampling method, namely the sampling of population members is done randomly. So that in this study using a sample of 96 customers for Bank Muamalat Indonesia Probolinggo Branch and as many as 97 customers at BSI KCP Probolinggo Sudirman. In this study, primary data was used, namely through a questionnaire using a measurement scale, namely the Likert scale. The method used in this research is multiple linear regression method. Based on the results of the T test, it shows that there is an effect of service quality of 38.75% on customer satisfaction at Bank Muamalat Indonesia Branch. smaller than 0.05, so H0 is rejected and Ha is accepted. Likewise with the results of the T-test of Bank Syariah Indonesia Kcp. Probolinggo Sudirman there is an effect of service quality of 30.68% on customer satisfaction. Based on the comparison test, there is a difference in the value of the influence of service quality on Bank Muamalat Indonesia Probolinggo Branch and Bank Syariah Indonesia Kcp. Probolinggo Sudirman by 8.07%. The influence given by service quality on customer satisfaction at Bank Muamalat Indonesia Probolinggo Branch is greater than Bank Syariah Indonesia Kcp. Probolinggo Sudirman.